Sorghum Grain Filling and Dry Down Dynamics for Hybrids Released Over the Past Six Decades in the US - P. A. Demarco; L. Mayor; P. V. Prasad; C. D. Messina; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2021)
Sorghum (Sorghum bicolorL. Moench) is mainly grown in the Great Plains region of the United States, with the state of Kansas as the premier cropland for its cultivation. Over time, improvements in sorghum have been related to genetic and management interactions, however, scarcity of information on the grain filling and the dry down processes have been reported. This study characterizes grain filling and dry down dynamics for hybrids with different released years. Field trials were conducted during the 2018 and 2019 seasons in Kansas, testing 20 commercially available grain sorghum hybrids released between 1963 and 2017. Grain dry matter accumulation and reduction in grain moisture content were determined during the reproductive period, from grain filling to the physiological maturity of the crop. Across decades (hybrids), no changes in grain filling duration and rate were documented. Over the past 60 years, the rate of seed filling ranged from 0.56 to 1.34 mg grain/day, and the duration varied from 30 to 40 days for sorghum hybrids. The dry down duration ranged from 16 to 32 days and the rate of dry down ranged from -0.64 to -0.99% of moisture per day. Despite the lack of statistical differences in these grain filling traits, information about duration and rate are valuable guiding points for farmers in the US to better understand the potential fit of this crop into more intensified rotations.
Keywords: sorghum; grain filling; dry down